Effects of Calcined Phosphogypsum on the Geotechnical Parameters of Fine-Grained Soils - Şenol, Ahmet (My University, 2019)
In this article, the using of waste materials has been studied such as phosphogypsum in the alteration of fine-grained soils in order to upgrade the geotechnical properties as a construction material. Standard Proctor test, unconfined compressive strength tests and California bearing ratio were carried out on Calcined Phosphogypsum (CPG) stabilized soil samples. It was determined that the phosphogypsum with additives calcined at the low temperature 150 ºC. Treatment with CPG generally reduces the maximum dry density but CPG increase the optimum moisture content. Compressive strength, California bearing ratio were performed to investigate effects of additive mixtures of stabilized and natural soil specimen. The empirical results show that stabilized samples with CPG additive mixtures have high durability as compared to unstabilized samples. These contribution blends have also improved the dynamic behaviors of the soil samples. As a result, we conclude that CPG additive mixtures can be completely used as an additive material to strength of granular soils in highway constructions and embankment applications. The experiment results understood that the stabilized fine-grained soil specimens containing CPG show high resistance to the CBR and unconfined compressive strengths as compared to natural fine-grained soil samples.
Keywords: Yeşil; Sürdürülebilir Bilim ve Teknoloji; İnşaat Mühendisliği; İnşaat ve Yapı Teknolojisi; Jeoloji; Çevre Mühendisliği